Cloud information security : a higher education perspective - Van der Schyff, Karl Izak (Rhodes University, Faculty of Science, Department of Computer Science, 2014)
In recent years higher education institutions have come under increasing financial pressure. This has not only prompted universities to investigate more cost effective means of delivering course content and maintaining research output, but also to investigate the administrative functions that accompany them. As such, many South African universities have either adopted or are in the process of adopting some form of cloud computing given the recent drop in bandwidth costs. However, this adoption process has raised concerns about the security of cloud-based information and this has, in some cases, had a negative impact on the adoption process. In an effort to study these concerns many researchers have employed a positivist approach with little, if any, focus on the operational context of these universities. Moreover, there has been very little research, specifically within the South African context. This study addresses some of these concerns by investigating the threats and security incident response life cycle within a higher education cloud. This was done by initially conducting a small scale survey and a detailed thematic analysis of twelve interviews from three South African universities. The identified themes and their corresponding analyses and interpretation contribute on both a practical and theoretical level with the practical contributions relating to a set of security driven criteria for selecting cloud providers as well as recommendations for universities who have or are in the process of adopting cloud computing. Theoretically several conceptual frameworks are offered allowing the researcher to convey his understanding of how the aforementioned practical concepts relate to each other as well as the concepts that constitute the research questions of this study.
Keywords: Cloud computing -- Security measures; Information technology -- Security measures; Data protection; Internet in higher education; Education, Higher -- Technological innovations